Increased Serum Interleukin-2 Levels Are Associated with Abnormal Peripheral Blood Natural Killer Cell Levels in Patients with Active Rheumatoid Arthritis - Baochen Li; Qiaoling Guo; Yanyan Wang; Rui Su; Chong Gao; Jinfang Zhao; Xiaofeng Li; Caihong Wang (Mediators of Inflammation)
Objective. To investigate the relationship between serum interleukin-2 (IL-2) levels and disease activity, absolute numbers of peripheral lymphocyte subsets, autoantibodies, and associated cytokines in patients with rheumatoid arthritis (RA). Methods. This study included 106 patients with RA, evaluated their disease activity (DAS28 score), and divided them into disease remission (DAS28≤2.6), low disease activity (DAS28≤3.2), and moderate-high disease activity (DAS28>3.2) groups. Flow cytometry was used to detect the absolute numbers of peripheral lymphocyte subpopulations and CD4+ T cell subsets in each group, and serum cytokine levels were measured using cytometric bead array. Results. Serum IL-2 levels in RA patients were positively correlated with disease activity and rheumatoid factor titers (p<0.001 and p=0.045, respectively), and multiple regression analysis revealed that serum IL-2 levels were an independent factor affecting disease activity. Serum IL-2 levels were positively correlated with Th17/Treg ratios (p=0.013). Compared with the remission group, peripheral lymphocyte and CD4+ T lymphocyte subsets in patients with active RA decreased to varying degrees; however, the numbers of peripheral natural killer (NK) cells were significantly higher in the moderate-high disease activity group than in the remission (p=0.046) and low disease activity (p=0.020) groups; the percentages of NK cells had the same trend. In addition, the number and percentage of NK cells were positively correlated with serum IL-2 levels (p=0.018 and p=0.006, respectively). Conclusions. In RA patients, serum IL-2 levels were not only correlated with patients’ disease activity and autoantibody levels but were also involved in their Th17/Treg immune imbalance. In addition, in patients with active RA, NK cell levels were abnormally elevated, possibly due to high serum levels of IL-2.